2022
DOI: 10.3390/ma15010359
|View full text |Cite
|
Sign up to set email alerts
|

Development of Antifouling Polysulfone Membranes by Synergistic Modification with Two Different Additives in Casting Solution and Coagulation Bath: Synperonic F108 and Polyacrylic Acid

Abstract: This study deals with the development of antifouling ultrafiltration membranes based on polysulfone (PSF) for wastewater treatment and the concentration and purification of hemicellulose and lignin in the pulp and paper industry. The efficient simple and reproducible technique of PSF membrane modification to increase antifouling performance by simultaneous addition of triblock copolymer polyethylene glycol-polypropylene glycol-polyethylene glycol (Synperonic F108, Mn =14 × 103 g mol−1) to the casting solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Based on the FTIR spectra in Figure 4 , it can be found that two strong characteristic peaks were observed at the wavelengths of 1489 and 1586 cm −1 for the pure PSf substrate [ 38 ], which indicates an aromatic vibrational bonding of C=C in the polysulfone group. Moreover, the peaks at the wavenumbers of 1151 and 1242 cm −1 are the vibrational bonding of O=S=O and C–O–C in the ether group.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the FTIR spectra in Figure 4 , it can be found that two strong characteristic peaks were observed at the wavelengths of 1489 and 1586 cm −1 for the pure PSf substrate [ 38 ], which indicates an aromatic vibrational bonding of C=C in the polysulfone group. Moreover, the peaks at the wavenumbers of 1151 and 1242 cm −1 are the vibrational bonding of O=S=O and C–O–C in the ether group.…”
Section: Resultsmentioning
confidence: 99%
“…The choice of these membranes is attributed to their moderate pure water flux and the surface roughness of the membrane selective layer ( Figure 8 , Figure 10 and Figure 11 a, Table 4 ). It is widely known that antifouling performance in ultrafiltration is determined by the pore size, surface roughness, hydrophilicity and zeta potential of the membrane selective layer [ 70 , 71 , 72 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
“…This technique can contribute to surface modification due to the embedding of hydrophilic polymers or polyelectrolytes into the selective layer, which yields changes in the hydrophilicity, roughness, charge and chemical composition of the membranes. This approach was developed and studied in [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…Polyacrylic acid (PAA) [ 48 , 49 , 53 ], polyethylene imine (PEI) [ 37 , 41 , 43 ], copolymers Praestol 859 [ 47 , 51 ] and Praestol 2540 [ 50 ], poly (diallyldimethylammonium chloride) [ 41 ], chitosan [ 55 ], zwitterionic copolymers [ 56 ], poly (sodium 4-styrenesulfonate) (PSS) [ 40 ], PVP [ 52 ] and PVA [ 54 ] were applied as additives to the coagulant for preparation of flat-sheet and hollow fiber membranes. There are different purposes which can be achieved by the addition of hydrophilic polymers and polyelectrolytes to precipitation medium: Increase in membrane antifouling performance [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 56 ]; Formation of a separation layer after subsequent cross-linking [ 37 , 38 ] or reaction with oppositely charged polyelectrolyte [ 37 , 40 , 41 , 42 , 45 , 46 ]; Creating an intermediate layer for preparation of the composite membrane via interfacial polymerization (IP) technique [ 44 ]; Tailoring membrane surface charge for enhanced separation of charged molecules [ 39 ]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation